Türk Halk Kültüründe El Sanatlarının Önemi: Kıbrıs Örneği / The Importance of Handicrafts in Turkish Folk Culture: The Case of Cyprus - Miralay, Fatma (Journal of History Culture and Art Research, 2018)
Abstract Handicrafts are one of the essential elements of Cypriot Turkish folk culture. The cultural diversity of Cyprus Island due to the fact that it was home to various cultures in different times reflected to the handicrafts as well. Handicrafts in Cyprus have mostly taken place for usage and commercial purposes in historical process; however, in modern times they are used as decorative objects. Handicrafts carry local features in the maintaining of traditions of Cypriot Turkish people and the sustainability of the values of Turkish culture. Rich in usage, make and material, Cypriot Turkish handicrafts can be generally examined under the titles of embroidery and wood engraving. Examples of embroidery or cotton weaving include Lefkara work, Lapta work, Koza work and needle lace. Dowry chest and geotextile are the most well-known examples of Cypriot Turkish wood engraving. All of the foregoing are important cultural elements of Cypriot Turkish identity. This paper examines the characteristic features of handicrafts belonging to Cypriot Turkish folk culture in technical and material terms; it also aims at revealing its place and importance in Cypriot Turkish social and cultural life. Öz El sanatları Kıbrıs Türk halk kültürünün önemli unsurların bir tanesidir. Kıbrıs Adasının farklı dönemlerde çeşitli kültürlere ev sahipliği yapmış olmasından kaynaklanan kültür çeşitliliği el sanatlarına da yansımıştır. Kıbrıs’ta el sanatları, tarihsel süreçte büyük ölçüde kullanım ve ticari amaçlı yer alırken, modern zamanlarda dekoratif obje olarak kullanılmıştır. Kıbrıs Türk halkının geleneklerinin sürdürülmesi ve Türk kültürü değerlerinin yaşatılmasında, el sanatları yöresel özellikler taşımaktadır. Kullanım, yapım ve malzeme açısından zengin olan Kıbrıs Türk el sanatları, genel olarak Nakış ve Ahşap Oymacılık başlıkları altında incelenebilir. Lefkara İşi, Lapta işi, Koza işi ve İğne Danteli nakış veya pamuklu dokuma türlerine örnek gösterilebilir. Çeyiz sandığı ve sesta işçilikleri (bitkisel örücülük) Kıbrıs Türk ahşap oymacılığının en iyi bilinen örnekleridirler. Tüm bunlar Kıbrıs Türk kimliğinin önemli kültürel unsurlarıdırlar. Bu araştırma, Kıbrıs Türk halk kültürüne ait el sanatlarının teknik ve malzeme açısından karateristik özelliklerinin incelenmesini ayrıca, Kıbrıs Türk sosyal ve kültürel yaşamındaki yeri ve önemini ortaya çıkarmayı hedeflemektedir.